1985
DOI: 10.1152/ajpendo.1985.249.3.e276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo gonadal hormone environment on in vitro hGRF-40-stimulated GH release

Abstract: The effects of gender and the gonadal hormone environment on basal and stimulated growth hormone (GH) release by dispersed and continuously perifused rat anterior pituitary cells were examined. Cells from intact male and diestrus day 2 female rats and from castrate male rats either untreated or treated with testosterone (T) or 17 beta-estradiol (E2) were used. Basal GH release (ng/min per 10(7) cells; mean +/- SE) by cells from diestrus day 2 female rats was less than by cells from castrate rats treated with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
18
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 14 publications
7
18
0
Order By: Relevance
“…Data gathered over the last few years have conclusively shown that GH secretion is sexually differentiated and in fluenced by in vivo gonadal environment [29][30][31][32], Thus pituitary GH content, amplitude of GH pulses and GH responses to GHRH are stimulated by testosterone and inhibited by estrogens. Available evidence suggests that gonadal steroids modulate GH secretion through differ ent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data gathered over the last few years have conclusively shown that GH secretion is sexually differentiated and in fluenced by in vivo gonadal environment [29][30][31][32], Thus pituitary GH content, amplitude of GH pulses and GH responses to GHRH are stimulated by testosterone and inhibited by estrogens. Available evidence suggests that gonadal steroids modulate GH secretion through differ ent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests that gonadal steroids modulate GH secretion through differ ent mechanisms. At the hypothalamic level they influence GHRH and somatostatin gene expression [33], At the pi tuitary level they have been shown to modulate the so matotroph responsiveness to different GH secretagogues [29,31,32]. Finally, gonadal steroids have been shown to influence the GH metabolic clearance rate [34], In this study we investigated the effect of gonadal steroids on so matotroph responsiveness to GHRP-6.…”
Section: Discussionmentioning
confidence: 99%
“…GH secretion is controlled by GHRH and somatostatin [ 1] and peripheral signals such as gonadal hormones [2,3], In adult rats, in vivo pituitary responsiveness to GHRH was shown to de crease after orchidectomy [2,3] and increased after testos terone administration [2, 4], Therefore, testicular factors other than testosterone may be involved in the modula tion of pituitary responsiveness to GHRH. This is because the in vitro GH response to GHRH remained unaltered after preincubation of dispersed cells with testosterone [2] and the increased serum testosterone levels in orchidec tomized males after testosterone administration were not accompanied by a full recovery of the in vitro pituitary response to GHRH [5]. In the present work we demon strate that GHRH-induced GH secretion decreased in or chidectomized males, and remained normal after sup pression of testosterone secretion by ethylene dimethane sulphonate (EDS).…”
mentioning
confidence: 50%
“…In vivo treatment with testosterone enhances, while in vivo treatment with estrogen diminishes in vitro GRF-stimulated GH release [33,34]. The effects of in vitro estrogen treatment on GH release and synthesis in culture are conflicting [30,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%